CREATIVE APPROACH TO DEVELOPMENT OF TEACHER COMPETENCES - Petr, MACH (Trends in education, 2008)
The paper deals with teaching competences in basic and specialized education. competences are becoming the most important attribute of innovation and modernization of the educational process.The purpose of own research was to study the attitudes of teachers in the Pilsen region to teaching competences by means of questionnaires followed by controlled discussion. The results of the research were used to determine the teaching competences hierarchy. The most important competences were later specified in greater detail. The research showed that the respondents regarded specialist and didactic competences as the most important.In its conclusion the paper deals with the creative approach to the development of teaching competences using the method of didactic case studies. This creative approach is being applied in the full-time study programmes for future teachers as well as in lifelong education.
Keywords: education; teaching competences; didactic competences; pedagogical research; creativity.